Development of Predict Observe Explain Based Flat Side Building Worksheets to Improve Students' Mathematical Representation Skills - Setiyani, Eka Nur; Panomram, Waratchaya; Wangdi, Tashi (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to knowing student and teacher responses to Predict Observe Explain based worksheets to develop students' mathematical representation abilities. Methodology: The type of research that will be used is research and development (R&D). In this research, the 4D device development research method (Four D Model) was used as a research and development procedure. The data collection technique in research on developing student work sheets uses a questionnaire. The data collection instrument used in this research is the product trial instrument. Data obtained through trial instruments were analyzed using qualitative descriptive statistics. Main Findings: Based on the results of questionnaire data on student responses in the small-scale and large-scale field trials, the mathematical media developed in the criteria for interpreting attractiveness, it is very interesting as a source of learning material and is suitable for use. Novelty/Originality of this study: This study found that the Predict Observe Explain -based flat-sided geometric worksheet is suitable for use in improving students' mathematical representation skills and getting a positive response from students and teachers. This research contributes to the development of innovative and effective learning tools in the context of mathematics learning.